Conflicting group memberships modulate neural activation in an emotional production-perception network. (May 2020) - Steines, Miriam; Krautheim, Johannes T.; Neziroğlu, Gizem; Kircher, Tilo; Straube, Benjamin
Abstract: Social group membership modulates the neural processing of emotional facial expressions, which, in turn, recruits part of the neural production system. However, little is known about how mixed – and potentially conflicting – social identity cues affect this mechanism. In this study, we tested the hypothesis that incongruent cues of two group memberships (ethnic and experimentally created minimal groups) elicit conflict processing for neutral and, in particular, angry facial expressions. We further expected this interaction of ethnic group, minimal group and emotion to also modulate activation in an emotional production-perception network. Twenty-two healthy German subjects saw dynamic angry and neutral facial expressions, presented in short video clips during functional MRI scanning. All depicted actors belonged to an ethnic in– or outgroup (German or Turkish descent) as well as an ad hoc experimentally created minimal in– or outgroup. Additionally, subjects produced angry or neutral expressions themselves. The whole-brain interaction of ethnic group, minimal group and emotion revealed activity in the right parietal lobule and left cerebellum. Both showed strongest activation for angry faces with conflicting group memberships (e.g., 'ethnic outgroup/minimal ingroup'). In addition, a sub-region of the left cerebellum cluster was also activated for both perceiving and producing angry versus neutral expressions. These results suggest that incongruent group members displaying angry facial expressions elicit conflict processing. Group interaction effects in an emotional production-perception network further indicate stronger neural resonance for incongruent group members.